Atomistic modeling of the infrared response of fullerenes under hydrostatic pressure. (31st October 2018) - Calvo, F; Parneix, P; Falvo, C
Abstract: The anharmonic infrared spectrum of individual C60 and C70 fullerenes under hydrostatic pressure was theoretically computed by means of atomistic simulations. Using a tight-binding model for the fullerenes and a simple particle-based pressure-transmitting fluid, the structural and vibrational properties were determined at room temperature and up to 20 GPa. All properties generally exhibit relative variations that are linear with increasing pressure, but whose magnitude can be comparable to pure thermal effects. The bond length contraction usually agrees with existing results, and for C70 our approach manages to reproduce the occasionally negative pressure coefficient found for some low-frequency modes in experiments.